2005
DOI: 10.1677/joe.1.05819e
|View full text |Cite
|
Sign up to set email alerts
|

Addendum to: Characterization of the resistance to the anorectic and endocrine effects of leptin in obesity-resistant rats fed a high-fat diet. Journal of Endocrinology 2004, 183 289-298

Abstract: The aim of our work was to compare the degree of leptin resistance in diet-induced obesity-prone and resistant rats, both in terms of reduction of feeding and of endocrine effects on somatotroph and thyroid axes. We concluded that both groups of rats show a selective resistance to the anorectic effect of leptin while the pathways mediating the neuroendocrine effects of the peptide were preserved.In our paper we omitted to acknowledge the study previously published by Levin and Dunn-Meynell (2002), which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Our results and those of others [21,31] demonstrate that at least 12 days or longer are required before the body weights of LFD and HFD mice and rats diverge. One possible explanation for the latency is that consumption of an HFD gradually induces changes in intestinal morphology and surface area, enterocyte function, and fatty acid transport such that the efficiency of nutrient absorption from the gut is increased [36,37].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results and those of others [21,31] demonstrate that at least 12 days or longer are required before the body weights of LFD and HFD mice and rats diverge. One possible explanation for the latency is that consumption of an HFD gradually induces changes in intestinal morphology and surface area, enterocyte function, and fatty acid transport such that the efficiency of nutrient absorption from the gut is increased [36,37].…”
Section: Discussionsupporting
confidence: 78%
“…Among these are the development of obesity with increased adiposity [4], and leptin and insulin resistance [1,21] characterized by reduced target cell sensitivity to leptin and insulin and increased circulating levels of the hormones. The increased body weights, adiposity and circulating hormones and glucose levels observed in the present study confirmed the expected phenotype of wild-type mice chronically consuming an HFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation